A Framework for Sustainable Urban Street Design - Bhagat, Anushree; Kumar, Ajay (Engineering, Technology & Applied Science Research, 2024)
Rapid urbanization worldwide poses sustainability issues. To address these issues, Sustainable Urban Streets (SUS) are being developed to balance social, economic, and environmental factors in street design. The main aim of this paper is to investigate the suitable SUS characteristics for metropolitan environments and to develop a framework for SUS design. This study creates a framework for SUS based on four main aspects: environmental sustainability, social sustainability, economic sustainability, and design sustainability. A rigorous search strategy, focusing on urban street design parameters within sustainability frameworks, has been employed through a Systematic Literature Review (SLR) using PRISMA meta-analysis and considering databases from Scopus and Web of Science (WoS). Subsequently, a comprehensive list has been compiled, encompassing all the parameters or attributes and their respective sub-parameters or indicators identified in the study. In the second part of the paper, three rounds of the Delphi technique were used to extract the Indian experts' opinions and to reach a consensus among the experts on the attributes and indicators identified through SLR. To determine the weightage of indicators, statistical computations were performed using SPSS software, which calculated the mean, Standard Deviation (SD), Interquartile Range (IQR), and Coefficient of Variation (CV). Finally, 19 primary attributes and 46 secondary indicators have eventually emerged, which may contribute towards four aspects of SUS design. These attributes and indicators will provide a framework to develop sustainable urban streets in metropolitan areas and foster sustainable development in the city.